ORIGINAL PAPERBack pain in women over 55 years – patogenetic analysis - Tłustochowicz, Małgorzata; Zakrzewska, Aleksandra; Śliwińska, Justyna (Reumatologia/Rheumatology, 2006)
The aim of the study was to assess the reason of low back pain in women over 55 years. Examined group consists of 103 women referred due to pain in lumbar spine. X-rays in A-P and side projections were performed and were analyzed by 2 independent radiologists. Radiological findings were revealed in 93% of examined women. The most frequent was dyscopathy (in 73.8%), with osteophytes in 37.3%, subchondrial sclerosis in 32% and spondylolisthesis in 14.6%. In 30.1 % was found spondyloarthritis, Baastrup changes in 17.5%. Fractures were found in 18.4%, the most frequently in L4 vertebra. All changes were more frequent in patients over 75, but differences were statistically insignificant.